Correlation of quantitative bone histology data with life history and climate: a phylogenetic approach. (August 2014) - Marín‐Moratalla, Nekane; Cubo, Jorge; Jordana, Xavier; Moncunill‐Solé, Blanca; Köhler, Meike
<x xml:space="preserve">Abstract</x> Growth rate is a fitness component that is determined by intrinsic (e.g. metabolism) and extrinsic (environment) factors, the relative importance of which remains to be ascertained. Vascular and cellular networks of primary compact bone tissue correlate with bone growth rate in vertebrates. Here, we aim to determine the main factor, either intrinsic or extrinsic, that shapes the vascular and cellular networks of fibrolamellar bone tissue. To do this, we examine the correlation of some life‐history traits in bovids, such as body mass at birth, adult body mass and relative age at reproductive maturity (relative to body mass) as a proxy of the species' pace of life, and climatic regimes, with quantitative data from bone histology in a phylogenetic context. We quantify vascular orientation and vascular and cell densities in 51 wild ruminants with known environmental conditions belonging to 26 species of bovids and one chevrotain. Our results show that the quantified histological variables do not correlate with broad climatic categories or with life history. Instead, they are related to body mass: larger bovids display more circular canals and lower cell densities than smaller bovids. We suggest the former is related to higher rates of periosteal bone deposition, whereas the latter is related to lower mass‐specific metabolic rates. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 678–687.